Pattern and management of sports injuries presented by Lagos state athletes at the 16th National Sports Festival (KADA games 2009) in Nigeria - Owoeye Oluwatoyosi BA (BMC, 2010)
Abstract Background There is a dearth of information on the epidemiology of sports injuries in Nigeria. The study was aimed at documenting sports injuries sustained by Lagos state athletes during the 16th National Sports Festival (KADA Games 2009). It was also aimed at providing information on treatments offered to injured athletes. Methods The study was carried out at Amadu Bello Stadium Complex, sporting arena of the Murtala Square and the team Lagos mini clinic. Participants were accredited Lagos state athletes who at one point in time during the games required treatment from any of the members of the medical team. Demographic data of athletes, type of injuries, body parts injured and treatment modalities used were documented and analysed using descriptive statistics. Results Within the period of the games, a total of 140 sports injuries were documented from 132 athletes with an approximate male to female ratio of 2:1 and age ranging from 15-38 years. Most of the injuries reported by the athletes were "minor" injuries. Muscle strain was the most common type of injury (31.4%) followed by ligament sprains (22.9%). The lower extremities were the most injured body region accounting for 50% of all injuries. Over 60% of injuries presented by the athletes were from basketball, cricket, hockey, rugby and baseball. Cryotherapy was the most frequently used treatment modality, followed by bandaging and massage with anti-inflammatory gels. Conclusion Establishing injury prevention programmes directed at the lower extremities may help reduce the risk of injuries to the lower extremities. Since cryotherapy was the most used treatment modality, it is suggested that it should be made abundantly available to the medical team preferably in forms of portable cold sprays for easy transportation and application during the games. It is also important that physiotherapists form the core of the medical team since they are trained to apply most of these treatment modalities and they also play a major role in establishing injury prevention routines. This data provides information that will be useful to both state and federal medical teams in preparing for future games.